Peningkatan Daya Saing Tenaga Kerja Sektor Agroindustri di Indonesia melalui Sertifikasi - ., Hidayat; Wibowo, Nugroho Mardi; Riswati, Fatimah; Humaidi, Faisol (Universitas Brawijaya, Indonesia, 2012)
in the long-term perspective, this study aims to improve Indonesia's competitiveness through theapplication of labor standardization. The specific objectives of this study was, first identify the areas ofcompetence that must be owned agro-industry sector workforce in Indonesia. Second, formulate a modelstrategy (grand strategy) agro-industry sector workforce development in Indonesia. Third,formulate aneffective policy alternatives to improve the competitiveness of agro-industry sector workforce inIndonesia. Fifth, to formulate indicators of competence as the basis for assessment of the labor certificationin agroindustry sector in Indonesia. The method of analysis used in this study were (a) Analysis of MappingFunctions work, EFI & EFE Matrix Analysis, SWOT Analysis, Policy Analysis, and Basic Function Analysis.Based on the analysis of the work function mapping got the result that the area of competence that mustbe owned by the agro-sector employment in Indonesia, namely 5 (five) key functions include 1) developmentprocess, 2) development of quality standards, 3) the technical development of packaging, 4) developmentof storage , and 5) development of marketing and business strategy. SWOT analysis results indicate thatthe agro-industry sector in workforce development is in quadrant III is a grand strategy to turnaroundstrategy.The alternative strategy of agro-industry sector workforce development in Indonesia includestrategies SO and WO of each there are 4 strategies, ST strategies totaling 3 and WT strategiesamounted to 2.Policy Analysis of the results obtained there are 30 alternative policies agro industrialsectorworkforce development. One is the restructuring of the Training Center by establishing a vocationaltraining center specialized agro-industry. The results of the analysis ofthe basic functions and processes inthe production of agro-industries can be generated 65 competence of workers in the agroindustrialsectorof Indonesia.